The Two Translationally Controlled Tumor Protein Genes, CsTCTP1 and CsTCTP2, Are Negative Modulators in the Cucumis sativus Defense Response to Sphaerotheca fuliginea - Meng, Xiangnan; Yu, Yang; Zhao, Junyue; Cui, Na; Song, Tiefeng; Yang, Yun; Fan, Haiyan (Frontiers in Plant Science, 2018)
Pathogen stress often significantly decreases cucumber production. However, knowledge regarding the molecular mechanism and signals of cucumber disease resistance is far from complete. Here, we report two translationally controlled tumor protein genes, CsTCTP1 and CsTCTP2, that are both negative modulators in the Cucumis sativus defense response to Sphaerotheca fuliginea. Subcellular localization analysis showed that CsTCTP1 and CsTCTP2 were both localized in the cytoplasm. Expression analysis indicated that the transcript levels of CsTCTP1 and CsTCTP2 were linked to the degree of cucumber resistance to S. fuliginea. Transient overexpression of either CsTCTP1 or CsTCTP2 in cucumber cotyledons impaired resistance to S. fuliginea, whereas silencing of either CsTCTP1 or CsTCTP2 enhanced cucumber resistance to S. fuliginea. The relationship of several defense-related genes and ABA and target of rapamycin (TOR) signaling pathway-related genes to the overexpressing and silencing of CsTCTP1/CsTCTP2 in non-infested cucumber plants was investigated. The results indicated that CsTCTP1 participates in the defense response to S. fuliginea by regulating the expression of certain defense-associated genes and/or ABA signaling pathway-associated genes, and CsTCTP2 participates through regulating the expression of TOR signaling pathway-associated genes. Our findings will guide enhancing the resistance of cucumber to powdery mildew.